In vitro Anti-parasitic Activity of Pelargonium X. asperum Essential Oil Against Toxoplasma gondii - Huang, Si-Yang; Yao, Na; He, Jia-Kang; Pan, Ming; Hou, Zhao-Feng; Fan, Yi-Min; Du, Aifang; Tao, Jian-Ping (Frontiers in Cell and Developmental Biology, 2021)
Toxoplasmosis is a global zoonotic disease, and one-third of the human population is chronically infected by Toxoplasma gondii. Due to the limited effectiveness and prominent side effects of the existing drugs, there is a dire need for the discovery of new therapeutic options in the treatment of toxoplasmosis. In this study, five essential oils (EO) were screened for their anti-parasitic activity against T. gondii. The cytotoxicity of essential oils was evaluated using the MTT assay on human foreskin fibroblast cells. The CC50 values of Eucalyptus globulus EO, Cupressus sempervirens EO, Citrus aurantifolia EO, Melaleuca alternifolia EO, and Pelargonium X. asperum (Pa) EO were found to be 22.74, 7.25, 15.01, 6.26, and 4.77 mg/ml, respectively. Only PaEO exhibited anti-parasitic activity, and inhibited the growth of T. gondii in a dose-dependent manner. In addition, treatment with PaEO, was found to reduce the volume of T. gondii tachyzoites and make their membrane surfaces rough. These results showed that PaEO was able to inhibit the growth of T. gondii by reducing invasion, which may be due to its detrimental effect on the ability of tachyzoites to move. These findings suggest that PaEO could be a potential anti-T. gondii drug, which may facilitate the development of new and effective treatments against toxoplasmosis.